Quantum Dots: Site‐Controlled Single‐Photon Emitters Fabricated by Near‐Field Illumination (Adv. Mater. 21/2018). Issue 21 (May 2018) - Biccari, Francesco; Boschetti, Alice; Pettinari, Giorgio; La China, Federico; Gurioli, Massimo; Intonti, Francesca; Vinattieri, Anna; Sharma, MayankShekhar; Capizzi, Mario; Gerardino, Annamaria; Businaro, Luca; Hopkinson, Mark; et al.
Abstract : In article number1705450, Francesco Biccari and co‐workers describe a novel and versatile approach for the post‐growth fabrication of site‐controlled, single‐photon‐emitting quantum dots. This approach, which deploys the hot spot of a near‐field microscope to locally remove hydrogen from nanometer‐sized regions of a standard GaAs/GaAsN:H/GaAs quantum well, features state‐of‐the‐art control over both the nanostructure position (<100 nm) and emission energy (≈20 meV).